Genomic and Functional Characterization of Environmental Strains of SDS-Degrading Pseudomonas spp., Providing a Source of New Sulfatases - Furmanczyk, Ewa M.; Lipinski, Leszek; Dziembowski, Andrzej; Sobczak, Adam (Frontiers in Microbiology, 2018)
Biochemical, physiological and genomic comparisons of two Pseudomonas strains, assigned previously to the P. jessenii subgroup, which are efficient SDS-degraders were carried out. A GO enrichment analysis showed that the genomes of SDS-degraders encode more genes connected with bacterial cell wall biosynthesis and alkanesulfonate monooxygenase activity than their closest relatives from the P. jessenii subgroup. A transcriptomic analysis of the most promising strain exposed to detergent suggests that although SDS can be later utilized as a carbon source, in early stages it influences cell envelope integrity, causing a global stress response followed by cell wall modification and induction of repair mechanisms. Genomes of the analyzed strains from P. jesseni group encode multiple putative sulfatases and their enzymatic activity was experimentally verified, which led to the identification of three novel enzymes exhibiting activity towards SDS. Two of the novel alkylsulfatases showed their highest activity at pH 8.0 and the temperature of 60°C or 70°C. One of the enzymes retained its activity even after one hour of incubation at 60°C. Ions like K+ and Mg2+ enhanced enzymatic activity of both proteins, whereas Cu2+ or EDTA had inhibitory effects.